2021
DOI: 10.3389/fphar.2021.744826
|View full text |Cite
|
Sign up to set email alerts
|

Anlotinib Inhibits PFKFB3-Driven Glycolysis in Myofibroblasts to Reverse Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease in which the normal alveolar network is gradually replaced by fibrotic scars. Current evidence suggests that metabolic alterations correlate with myofibroblast activation in IPF. Anlotinib has been proposed to have antifibrotic effects, but the efficacy and mechanisms of anlotinib against lung fibrosis have not been systematically evaluated. The antifibrotic effects of anlotinib were evaluated in bleomycin-induced mouse models and transforming growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Prior reports indicate that hypoxia can induce fibroblast differentiation in normal fibroblasts (Chen, Zhang, et al, 2021; Kottmann et al, 2015). These findings suggest that α‐SMA expression is modulated when control fibroblasts are exposed to hypoxic conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Prior reports indicate that hypoxia can induce fibroblast differentiation in normal fibroblasts (Chen, Zhang, et al, 2021; Kottmann et al, 2015). These findings suggest that α‐SMA expression is modulated when control fibroblasts are exposed to hypoxic conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Here, however, our study provided the evidence that anlotinib could attenuate tumor growth through direct disturbance of lipid metabolism in LUAD cells. It has been shown that anlotinib could inhibit glycolysis in myofibroblasts to reverse pulmonary fibrosis, which indicates that anlotinib might be capable of interfering with nutrition metabolism in cancer cells, thereby eliciting killing effects (19). A recent study also showed that anlotinib could interfere with amino acid metabolism in colon cancer cells leading to impaired protein synthesis and disruption of energy supply (20), which indicates that the killing effect of anlotinib in cancer cells is linked to metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PFKFB3 expression can be increased by the secretion of TNF-α in lung fibroblasts, while PFKFB3 suppression effectively blocks TNF-α-induced aerobic glycolysis and lactate production in fibroblasts ( Xu et al, 2022 ). The anti-fibrotic effect of Anlotinib is demonstrated to inhibit PFKFB3-dependent glycolysis, which can be post-transcriptionally regulated by the RNA-binding protein PCBP3 ( Chen et al, 2021 ).…”
Section: Myofibroblastsmentioning
confidence: 99%